2019
DOI: 10.1002/ps.5255
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dermal and inhalation exposure to chlorantraniliprole assessed by using whole‐body dosimetry in Korea

Abstract: BACKGROUND We determined the characteristics and evaluated associated risks of sprayed pesticide exposure among workers cultivating Korean cabbage. The test pesticide, a mixture of 3% chlorantraniliprole and 4% indoxacarb wettable granules diluted 2000 times, was sprayed on Korean cabbage within a 3000 m2 area in Goesan, Korea. Dermal exposures were measured using a whole‐body dosimetry method. RESULTS Exposure to chlorantraniliprole was observed among ten individuals, ranging from 140.4 to 4234.0 µg person−1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…In general, unit exposure was much lower in seedcoating than in conventional spraying methods such as knapsack pesticide exposure to seed coating workers www.soci.org spray. [32][33][34] We confirmed that unit exposure depended on the type of work undertaken, as previously reported by others. 35 At the same level of chemical exposure, it is expected that less-toxic pesticides pose a lower risk to operating workers than highly toxic pesticides.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, unit exposure was much lower in seedcoating than in conventional spraying methods such as knapsack pesticide exposure to seed coating workers www.soci.org spray. [32][33][34] We confirmed that unit exposure depended on the type of work undertaken, as previously reported by others. 35 At the same level of chemical exposure, it is expected that less-toxic pesticides pose a lower risk to operating workers than highly toxic pesticides.…”
Section: Discussionsupporting
confidence: 90%
“…We showed that unit exposure was correlated less with the physical and chemical properties of the pesticide but had a large connection with the type of work undertaken. In general, unit exposure was much lower in seed‐coating than in conventional spraying methods such as knapsack spray 32–34 . We confirmed that unit exposure depended on the type of work undertaken, as previously reported by others 35 .…”
Section: Discussionsupporting
confidence: 89%
“…In pepper fields, characterized by high plant density and closely spaced rows, workers frequently interact with crops. This pattern is consistent with previous research on Korean cabbage, rice, and pepper, where body parts at the same height as the crops showed higher exposure distribution 8 , 25 , 41 , 44 , 49 . Dermal exposure on inner clothing during application ranged from 0.025 to 4.763 mg.…”
Section: Resultssupporting
confidence: 92%
“…In this study, we employed the WBD method to assess dermal exposure and the distribution patterns throughout the entire body of agricultural workers during the mixing/loading and application phases 8 . Table 1 and Table S3 presents data on dermal and inhalation exposure and distribution specifically for chlorothalonil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation